PEMBUATAN PROTOTYPE ALAT MONITORING KUALITAS AIR BERBASIS INTERNET OF THINGS (IOT) - Muh Ashley Mefgherry David; Revida Iriana (Asosiasi Dosen Muda Indonesia, 2024)
Based on data released by the Directorate General of Aquaculture in 2016, Indonesia occupies the top position in terms of total fish production in the world. Therefore, marine product trade is used as an important source of income for Indonesia and marine food products contribute greatly to food and nutritional security, employment and national economic growth. Water quality really needs to be paid attention to by farmers in order to minimize fish deaths during cultivation. Several important factors in fish cultivation are the level of salt content in the water, temperature and pH. Fish farmers are currently faced with big challenges in monitoring the water quality of fish farming ponds quickly and accurately. In general, fish farmers find out water quality manually, namely by taking samples of pond water to take to the laboratory. This is caused by several factors, including the physical distance between the cultivation site and the laboratory, the time required for sample collection, and the time-consuming analysis process. As a result, farmers are less able to take quick action to correct unsuitable water conditions, resulting in potential losses in fish farming. In order to help fish farmers, we need to create a PROTOTYPE OF WATER QUALITY MONITORING TOOLS BASED ON THE INTERNET OF THINGS. Making a prototype using the SDLC method which consists of several stages, namely analysis, design, implementation and testing. The output of this research is a prototype tool that is able to provide information about water quality, so that it can be a valuable support for fish farmers.